Nonaqueous electrolyte secondary battery
By attaching sulfonic acid compounds to the positive electrode active material of the nonaqueous electrolyte secondary battery and using a partition having a heat-resistant layer of a predetermined thickness, the problem in the prior art is solved that it is difficult to achieve high capacity and excellent high temperature storage characteristics at the same time, and efficient battery performance is achieved.
Patent Information
- Application Number
- CN202380059868.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-26
- Filing Date
- 2023-07-27
- Publication Date
- 2025-03-28
AI Technical Summary
The prior art is difficult to achieve high capacity and excellent high temperature storage characteristics simultaneously in non-aqueous electrolyte secondary batteries.
Non-aqueous electrolyte secondary battery is constructed by attaching a sulfonic acid compound to the surface of the particles containing the lithium composite oxide and using a partition having a heat-resistant layer of a predetermined thickness.
It achieves high capacity while improving the high-temperature storage characteristics, inhibits the dissolution of metals such as Ni, and improves the performance of the battery under high-temperature environment.
Smart Images

Figure CN119731821A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a nonaqueous electrolyte secondary battery. Background Art
[0002] Patent document 1 proposes that Li4Ti5O 12 An active material having a surface layer composed of a lithium sulfonate compound formed on the surface of lithium titanate particles as a main component. Patent Document 1 states that by using this active material in a negative electrode active material, a change in resistance before and after charge storage of a battery can be suppressed.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2018-6164 Summary of the invention
[0006] In non-aqueous electrolyte secondary batteries, it is an important issue to improve high temperature storage characteristics while ensuring high capacity. The existing technologies including Patent Document 1 cannot fully address such issues, and there is still much room for improvement.
[0007] A non-aqueous electrolyte secondary battery as one embodiment of the present invention is characterized in that it comprises a positive electrode, a negative electrode, a separator separating the positive electrode and the negative electrode from each other, and a non-aqueous electrolyte, the positive electrode comprises a lithium-containing composite oxide and a sulfonic acid compound present on the surface of particles of the lithium-containing composite oxide, the sulfonic acid compound is a compound represented by formula (I), the separator comprises a substrate layer and a heat-resistant layer formed on the surface of the substrate layer, and the heat-resistant layer is at least opposite to the positive electrode, and the thickness T1 of the substrate layer and the thickness T2 of the heat-resistant layer satisfy the relationship T2 / T1≥0.2.
[0008]
[0009] (In the formula, A is a Group 1 or Group 2 element, R is a hydrocarbon group, and n is 1 or 2.)
[0010] The nonaqueous electrolyte secondary battery disclosed herein has a high capacity and is excellent in high-temperature storage characteristics. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 It is a cross-sectional view of a nonaqueous electrolyte secondary battery as an example of the embodiment.
[0012] Figure 2 This is a diagram showing an example of a cross section of a separator. DETAILED DESCRIPTION
[0013] Even if the lithium titanate described in Patent Document 1 is used for the positive electrode, the reaction potential is low and the battery capacity is also reduced. The research results of the present inventors show that by allowing the sulfonic acid compound shown in the above formula (I) to be present on the particle surface of the lithium-containing composite oxide used as the positive electrode active material, a non-aqueous electrolyte secondary battery with high capacity and low resistance can be achieved. It is believed that the reason is that the reaction resistance in the positive electrode is reduced by the function of the sulfonic acid compound, and the charge and discharge depth can be deepened. However, as the charge and discharge depth deepens due to the reduction in reaction resistance, a new issue of reduced high-temperature storage characteristics is generated. It is believed that the main reason for the reduction in the above-mentioned high-temperature storage characteristics is that the dissolution amount of metals such as Ni contained in the lithium-containing composite oxide increases due to the deepening of the charge and discharge depth.
[0014] Therefore, the present inventors have successfully improved the high temperature storage characteristics while ensuring high capacity by using a lithium-containing composite oxide having a specific sulfonic acid compound attached to the particle surface as a positive electrode active material and using a separator having a heat-resistant layer of a predetermined thickness. According to the nonaqueous electrolyte secondary battery disclosed herein, even if the charge and discharge depth of the positive electrode is deep, the dissolution of metals such as Ni can be suppressed, so it is considered that the high temperature storage characteristics are improved.
[0015] The sulfonic acid compound represented by the above formula (I) exerts a specific function when applied to the surface of particles containing lithium composite oxide, reduces the reaction resistance in the positive electrode, and deepens the charge and discharge depth of the positive electrode. However, if the sulfonic acid compound is only applied to the positive electrode, a battery with high capacity and excellent high-temperature storage characteristics cannot be achieved. The research results of the present inventors show that in order to realize such a battery, it is important to use a separator having a heat-resistant layer of a specified thickness as described above.
[0016] Specifically, it was found that in a separator having a base layer with a thickness of T1 and a heat-resistant layer with a thickness of T2, the high-temperature storage characteristics were specifically improved when T2 / T1≥0.2 compared with when T2 / T1<0.2 (see Examples described below).
[0017] Hereinafter, an example of an embodiment of the non-aqueous electrolyte secondary battery disclosed in the present invention will be described in detail with reference to the accompanying drawings. It should be noted that the configuration formed by selectively combining the various structural features of the multiple embodiments and modified examples described below is included in the scope of the present invention. It should be noted that in this specification, "~" refers to a range including the upper and lower limits before and after "~".
[0018] Hereinafter, as a non-aqueous electrolyte secondary battery, a cylindrical battery in which a wound electrode body 14 is housed in an outer can 16 having a bottomed cylindrical shape is exemplified, but the outer shell of the battery is not limited to a cylindrical outer can. The non-aqueous electrolyte secondary battery disclosed herein may be, for example, a square battery having a square outer can, a coin-shaped battery having a coin-shaped outer can, or a bag-shaped battery having an outer shell composed of a laminate sheet including a metal layer and a resin layer. In addition, the electrode body is not limited to a wound type, and may also be a stacked electrode body in which a plurality of positive electrodes and a plurality of negative electrodes are alternately stacked with a separator.
[0019] Figure 1 FIG. 1 is a cross-sectional view of a nonaqueous electrolyte secondary battery 10 as an example of an embodiment. Figure 1 As shown, the nonaqueous electrolyte secondary battery 10 includes a wound electrode body 14, a nonaqueous electrolyte, and an outer can 16 for storing the electrode body 14 and the nonaqueous electrolyte. The electrode body 14 includes a positive electrode 11, a negative electrode 12, and a separator 13, and has a wound structure in which the positive electrode 11 and the negative electrode 12 are wound in a spiral shape with the separator 13 interposed therebetween. The outer can 16 is a metal container in a bottomed cylindrical shape with one end side open in the axial direction, and the opening of the outer can 16 is blocked by a sealing body 17. In the following, for convenience of description, the sealing body 17 side of the battery is set as the upper side, and the bottom side of the outer can 16 is set as the lower side.
[0020] The non-aqueous electrolyte comprises a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. The non-aqueous solvent may be, for example, esters, ethers, nitriles, amides, and mixed solvents of two or more thereof. As an example of a non-aqueous solvent, ethylene carbonate (EC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and mixed solvents thereof may be cited. The non-aqueous solvent may also contain a halogen substituted product (for example, fluoroethylene carbonate, etc.) in which at least a portion of the hydrogen in these solvents is replaced by a halogen atom such as fluorine. The electrolyte salt may be, for example, a lithium salt such as LiPF6.
[0021] The positive electrode 11, the negative electrode 12, and the separator 13 constituting the electrode body 14 are all strip-shaped long bodies, and are alternately stacked in the radial direction of the electrode body 14 by being wound into a spiral shape. The negative electrode 12 is formed to be one circle larger than the positive electrode 11 to prevent the precipitation of lithium. That is, the negative electrode 12 is formed longer than the positive electrode 11 in the length direction and the width direction. The separator 13 is formed to be at least one circle larger than the positive electrode 11, for example, two sheets are arranged in a manner of clamping the positive electrode 11. The electrode body 14 has a positive electrode lead 20 connected to the positive electrode 11 by welding or the like, and a negative electrode lead 21 connected to the negative electrode 12 by welding or the like.
[0022] Insulating plates 18 and 19 are disposed above and below the electrode body 14 , respectively. Figure 1In the example shown, the positive electrode lead 20 extends toward the sealing body 17 through the through hole of the insulating plate 8, and the negative electrode lead 21 extends toward the bottom side of the outer can 16 through the outside of the insulating plate 19. The positive electrode lead 20 is connected to the lower surface of the internal terminal plate 23 of the sealing body 17 by welding or the like, and the top plate of the sealing body 17, that is, the lid 27 electrically connected to the internal terminal plate 23, serves as the positive terminal. The negative electrode lead 21 is connected to the bottom inner surface of the outer can 16 by welding or the like, and the outer can 16 serves as the negative terminal.
[0023] A gasket 28 is provided between the outer can 16 and the sealing body 17 to ensure the airtightness inside the battery. A groove portion 22 is formed on the outer can 16, in which a part of the side portion protrudes inward and supports the sealing body 17. The groove portion 22 is preferably formed in an annular shape along the circumferential direction of the outer can 16, and the sealing body 17 is supported by its upper surface. The sealing body 17 is fixed to the upper part of the outer can 16 through the groove portion 22 and the open end of the outer can 16 fastened to the sealing body 17.
[0024] The sealing body 17 has a structure in which an internal terminal plate 23, a lower valve body 24, an insulating member 25, an upper valve body 26 and a cover 27 are stacked in order from the electrode body 14 side. The components constituting the sealing body 17 have, for example, a disc shape or a ring shape, and the components except the insulating member 25 are electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected at their respective central portions, and an insulating member 25 is sandwiched between their respective peripheral portions. When the internal pressure of the battery rises due to abnormal heat release, the lower valve body 24 is deformed and broken in a manner that pushes the upper valve body 26 toward the cover 27 side, thereby cutting off the current path between the lower valve body 24 and the upper valve body 26. When the internal pressure rises further, the upper valve body 26 breaks, and the gas is discharged from the opening of the cover 27.
[0025] Hereinafter, the positive electrode 11 , the negative electrode 12 , and the separator 13 constituting the electrode body 14 , and in particular, the positive electrode active material constituting the positive electrode 11 and the separator 13 will be described in detail.
[0026] [positive electrode]
[0027] The positive electrode 11 has a positive electrode core 30 and a positive electrode mixture layer 31 disposed on the surface of the positive electrode core 30. The positive electrode core 30 can use a foil of a metal such as aluminum that is stable within the potential range of the positive electrode 11, a thin film of the metal disposed on the surface, or the like. The positive electrode mixture layer 31 contains a positive electrode active material, a conductive agent, and a binder, and is preferably disposed on both sides of the positive electrode core 30 except for the portion connected to the positive electrode lead 20. The positive electrode 11 can be manufactured, for example, by applying a positive electrode mixture slurry containing a positive electrode active material, a conductive agent, and a binder to the surface of the positive electrode core 30, drying the coating, and then compressing to form the positive electrode mixture layer 31 on both sides of the positive electrode core 30.
[0028] As the conductive agent contained in the positive electrode mixture layer 31, carbon black such as acetylene black and Ketjen black, graphite, carbon nanotubes (CNT), carbon nanofibers, graphene and other carbon materials can be exemplified. As the binder contained in the positive electrode mixture layer 31, fluorine-containing resins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polyimide, acrylic resin, polyolefin, etc. can be exemplified. In addition, these resins can also be used in combination with carboxymethyl cellulose (CMC) or its salt, polyethylene oxide, etc. The content of the conductive agent and the binder is, for example, 0.1% by mass to 5% by mass relative to the mass of the positive electrode mixture layer 31.
[0029] The positive electrode 11 includes a lithium-containing composite oxide and a sulfonic acid compound present on the surface of the composite oxide particles. The lithium-containing composite oxide with the sulfonic acid compound attached to the particle surface functions as a positive electrode active material. The sulfonic acid compound is a compound represented by formula (I).
[0030]
[0031] In the formula, A is a Group 1 or Group 2 element, R is a hydrocarbon group, and n is 1 or 2.
[0032] The sulfonic acid compound represented by formula (I) (hereinafter, sometimes referred to as "sulfonic acid compound"), when applied to the surface of particles of the lithium-containing composite oxide, specifically functions to reduce the reaction resistance in the positive electrode 11 and improve the output characteristics of the battery. In addition, as the resistance is reduced, it becomes possible to deepen the depth of charge and discharge, and high capacity can be achieved. The sulfonic acid compound exerts this effect even in a very small amount, but the amount of the sulfonic acid compound present on the surface of the lithium-containing composite oxide is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, and particularly preferably 0.1% by mass or more relative to the mass of the lithium-containing composite oxide.
[0033] From the viewpoint of increasing capacity, the amount of the sulfonic acid compound present on the surface of the lithium-containing composite oxide is preferably 2 mass % or less, more preferably 1.5 mass % or less, and particularly preferably 1.0 mass % or less, based on the mass of the lithium-containing composite oxide.
[0034] The positive electrode active material may be a composite particle containing a lithium composite oxide with a sulfonic acid compound attached to the particle surface as a main component, and may be substantially composed of only the composite particle. It should be noted that, within the scope of not impairing the purpose of the present disclosure, the positive electrode active material may also contain a composite oxide or other compound other than the composite particle. For example, as part of the positive electrode active material, a composite oxide without a sulfonic acid compound attached to the particle surface may also be included.
[0035] The lithium-containing composite oxide preferably has a layered rock salt structure. When the sulfonic acid compound is applied to the composite oxide with a layered rock salt structure, the above effect becomes more significant. As the layered rock salt structure of the lithium-containing composite oxide, for example, a layered rock salt structure belonging to the space group R-3m, a layered rock salt structure belonging to the space group C2 / m, etc. can be listed. Among them, from the viewpoint of high capacity and stability of the crystal structure, a layered rock salt structure belonging to the space group R-3m is preferred. The layered rock salt structure of the lithium-containing composite oxide includes a transition metal layer, a Li layer and an oxygen layer.
[0036] The lithium-containing composite oxide is a composite oxide containing metal elements such as Ni, Co, Al, and Mn in addition to Li. The metal elements constituting the lithium-containing composite oxide are, for example, Ni, Co, and M (M is at least one element selected from the group consisting of Al, Mn, Fe, Ti, Si, Nb, Mo, W, and Zn). Among them, it is preferred to contain at least one selected from Ni, Co, Al, and Mn. As an example of a suitable composite oxide, a composite oxide containing Ni, Co, and Al and a composite oxide containing Ni, Co, and Mn can be cited.
[0037] From the viewpoint of high capacity, the lithium-containing composite oxide preferably contains 80 mol% or more of Ni relative to the total molar number of metal elements other than Li. In addition, the effect of adding the sulfonic acid compound is more significant when a lithium-containing composite oxide with a high Ni content is used. The Ni content relative to the total molar number of metal elements other than Li can be 87 mol% or more, or 90 mol% or more. The upper limit of the Ni content is, for example, 95 mol%.
[0038] As described above, an example of a suitable lithium-containing composite oxide is a composite oxide containing Ni, Co and M. The content of Co is, for example, 0 mol% to 20 mol% relative to the total molar number of metal elements other than Li. The content of M is, for example, 0 mol% to 20 mol% relative to the total molar number of metal elements other than Li. Co may not be substantially added, but battery performance is improved by adding a small amount of Co. M preferably includes at least one of Mn and Al.
[0039] For example, a lithium-containing composite oxide is a general formula Li a Ni x Co y M z O 2-b(wherein, 0.95≤a≤1.2, 0.80≤x≤0.95, 0≤y≤0.20, 0≤z≤0.20, 0≤b≤0.05, x+y+z=1, and M is at least one element selected from the group consisting of Al, Mn, Fe, Ti, Si, Nb, Mo, W, and Zn). Preferably, x in the above general formula is 0.87≤x≤0.95.
[0040] The content of elements constituting the lithium-containing composite oxide can be measured using an inductively coupled plasma atomic emission spectrometer (ICP-AES), an electron probe microanalyzer (EPMA), an energy dispersive X-ray analyzer (EDX), or the like.
[0041] The lithium-containing composite oxide is, for example, a secondary particle formed by the aggregation of multiple primary particles. The volume-based median particle size (D50) of the composite oxide is not particularly limited, and as an example, it is 3 μm to 30 μm, preferably 5 μm to 25 μm. In the case where the composite oxide is a secondary particle formed by the aggregation of primary particles, the D50 of the composite oxide refers to the D50 of the secondary particle. D50 refers to the particle size at which the cumulative frequency from the smaller particle size in the volume-based particle size distribution becomes 50%, also known as the median diameter. The particle size distribution of the composite oxide (the same is true for the negative electrode active material) is measured using a laser diffraction particle size distribution measuring device (for example, Microtrac Bell Co., Ltd., MT3000II) and water as the dispersion medium.
[0042] The average particle size of primary particles constituting the lithium-containing composite oxide is, for example, 0.05 μm to 1 μm. The average particle size of the primary particles is calculated by averaging the diameters of the circumscribed circles of the primary particles extracted by analyzing a scanning electron microscope (SEM) image of a cross section of the secondary particles.
[0043] As described above, the sulfonic acid compound present on the surface of the particles of the lithium-containing composite oxide is a compound represented by formula (I).
[0044]
[0045] In the formula, A is an element of Group 1 or Group 2, R is a hydrocarbon group, and n is 1 or 2. A is preferably an element of Group 1. Among them, Li or Na is more preferred, and Li is particularly preferred.
[0046] In formula (I), R is preferably an alkyl group. The carbon number of the alkyl group is preferably 5 or less, more preferably 3 or less. From the viewpoint of reducing the reaction resistance, an example of a suitable R is an alkyl group having a carbon number of 3 or less, wherein a methyl group is preferred. It should be noted that, in R, a portion of the hydrogen bonded to the carbon may also be substituted by fluorine. In addition, n in formula (I) is preferably 1.
[0047] Specific examples of the sulfonic acid compound include lithium methanesulfonate, lithium ethanesulfonate, lithium propanesulfonate, sodium methanesulfonate, sodium ethanesulfonate, magnesium methanesulfonate, lithium fluoromethanesulfonate, etc. Among them, at least one selected from the group consisting of lithium methanesulfonate, lithium ethanesulfonate and sodium methanesulfonate is preferred, and lithium methanesulfonate is particularly preferred.
[0048] The sulfonic acid compound is present, for example, homogeneously on the entire surface of the particles of the lithium-containing composite oxide. The presence of the sulfonic acid compound on the surface of the particles of the composite oxide can be confirmed by Fourier transform infrared spectroscopy (FT-IR). In the infrared absorption spectrum obtained by FT-IR, the positive electrode active material containing lithium methanesulfonate, for example, has a peak at 1238 cm -1 、1175cm -1 、1065cm -1 、785cm -1 There is an absorption peak near 1238cm -1 、1175cm -1 、1065cm -1 The peaks near 785cm are caused by the SO stretching vibration of lithium methanesulfonate. -1 The nearby peaks are peaks derived from CS stretching vibration of lithium methanesulfonate.
[0049] For positive electrode active materials containing sulfonic acid compounds other than lithium methanesulfonate, the presence can also be confirmed by the absorption peak derived from the sulfonic acid compound in the infrared absorption spectrum. It should be noted that the presence of the sulfonic acid compound on the surface of the particles of the lithium-containing composite oxide can also be confirmed by ICP, atomic absorption spectrometry, X-ray photoelectron spectroscopy (XPS), radioactive light XRD measurement, TOF-SIMS, etc.
[0050] The positive electrode active material as an example of the embodiment can be produced by the following method. It should be noted that the production method described here is an example, and the production method of the positive electrode active material is not limited to this method.
[0051] First, a metal oxide containing metal elements such as Ni, Co, Al, and Mn is synthesized. Then, the metal oxide and a lithium compound are mixed and calcined to obtain a lithium-containing composite oxide. The metal oxide is synthesized, for example, by stirring a solution of a metal salt containing Ni, Co, Al, Mn, etc. while dropping an alkaline solution such as sodium hydroxide, adjusting the pH to the alkaline side (for example, 8.5 to 12.5), thereby precipitating a composite hydroxide containing metal elements such as Ni, Co, Al, and Mn (coprecipitation), and heat-treating the composite hydroxide to synthesize the metal oxide. The heat treatment temperature is not particularly limited, and as an example, it is 300°C to 600°C.
[0052] Examples of lithium compounds include Li2CO3, LiOH, Li2O2, Li2O, LiNO3, LiNO2, Li2SO4, LiOH·H2O, LiH, and LiF. The metal oxide and the lithium compound are mixed, for example, in a molar ratio of the metal element in the metal oxide to Li in the lithium compound of 1:0.98 to 1:1.1. It should be noted that when mixing the metal oxide and the lithium compound, other metal raw materials may be added as needed.
[0053] The mixture of the metal oxide and the lithium compound is calcined, for example, in an oxygen atmosphere. The mixture may also be calcined through multiple temperature rising processes. The calcining process includes: a first temperature rising process of heating to 450°C to 680°C at a temperature rising rate of, for example, 1.0°C / min to 5.5°C / min, and a second temperature rising process of heating to a temperature exceeding 680°C at a temperature rising rate of 0.1°C / min to 3.5°C / min. The maximum reaching temperature of the calcining process may be set to 700°C to 850°C, and may be maintained at this temperature for 1 hour to 10 hours.
[0054] Next, the calcined product (containing lithium composite oxide) is washed with water and dehydrated to obtain a cake-like composition. The residual alkali component is removed by this washing process. The washing and dehydration can be carried out by existing known methods. Next, the cake-like composition is dried to obtain a powdery composition. The drying process can also be carried out under a vacuum atmosphere. An example of drying conditions is 0.5 hours to 15 hours at a temperature of 150°C to 400°C.
[0055] The sulfonic acid compound is added to the cake-like composition obtained in the washing step, for example, or to the powder-like composition obtained in the drying step. At this time, a sulfonic acid solution may be added instead of the sulfonic acid compound or together with the sulfonic acid compound. Thus, a positive electrode active material having a sulfonic acid compound attached to the surface of particles of the lithium-containing composite oxide can be obtained. The sulfonic acid compound may be added as an aqueous dispersion. In addition, the sulfonic acid solution is preferably an aqueous solution of sulfonic acid. The concentration of sulfonic acid in the sulfonic acid solution is, for example, 0.5% by mass to 40% by mass.
[0056] It should be noted that a certain amount of lithium compound remains in the cake-like composition, so by adding a sulfonic acid solution to the cake-like composition, Li dissolved in water in the cake reacts with the sulfonic acid to obtain lithium sulfonate. It should be noted that the approximate total amount of the added sulfonic acid compound remains on the surface of the lithium-containing composite oxide.
[0057] [negative electrode]
[0058] The negative electrode 12 includes a negative electrode core 40 and a negative electrode mixture layer 41 disposed on the surface of the negative electrode core 40. The negative electrode core 40 may be made of a foil of a metal such as copper that is stable within the potential range of the negative electrode 12, or a thin film having the metal disposed on the surface. The negative electrode mixture layer 41 includes a negative electrode active material and a binder, and is preferably disposed on both sides of the negative electrode core 40 except for a portion connected to the negative electrode lead 21. The negative electrode 12 is manufactured, for example, by applying a negative electrode mixture slurry including a negative electrode active material and a binder to the surface of the negative electrode core 40, drying the coating, and then compressing the coating to form the negative electrode mixture layer 41 on both sides of the negative electrode core 40.
[0059] The negative electrode active material contained in the negative electrode mixture layer 41 is not particularly limited as long as it is a material that can reversibly absorb and release lithium ions, and carbon materials such as graphite are generally used. The graphite can be any one of natural graphite such as flaky graphite, block graphite, and earthy graphite, block artificial graphite, and artificial graphite such as graphitized mesophase carbon microbeads.
[0060] The negative electrode active material includes, for example, a combination of carbon materials such as graphite and silicon materials. The negative electrode active material contains, for example, 1% by mass or more of silicon materials relative to the total mass of the negative electrode active material. This allows the battery to have a higher capacity. In addition, the silicon material has a large expansion ratio during charging, so the positive electrode 11 is close to the separator 13, and the separator 13 is easily oxidized. Therefore, when the negative electrode contains a silicon material, the effect of the heat-resistant layer 51 of the separator 13 described later is significantly manifested. The upper limit of the content of the silicon material is, for example, 20% by mass relative to the total mass of the negative electrode active material. Examples of the silicon material include Si, an alloy containing Si, and a SiO x (x is 0.5 to 1.6) represented by silicon oxide, in Li 2y SiO (2+y) A silicon-containing material in which Si fine particles are dispersed in a lithium silicate phase and a silicon-containing material in which Si fine particles are dispersed in a carbon phase, etc., represented by (0<y<2).
[0061] As the binder contained in the negative electrode mixture layer, for example, styrene butadiene rubber (SBR), nitrile rubber (NBR), carboxymethyl cellulose (CMC) or its salt, polyacrylic acid (PAA) or its salt (can also be PAA-Na, PAA-K, etc., or partially neutralized salt), polyvinyl alcohol (PVA), etc. These can be used alone or in combination of two or more.
[0062] [Separator]
[0063] The separator 13 separates the positive electrode 11 and the negative electrode 12 from each other. The separator 13 includes a base material layer and a heat-resistant layer formed on the surface of the base material layer. Figure 2 It is a cross-sectional view of the separator 13 as an example of embodiment. Figure 2 In the example shown, the separator 13 includes a substrate layer 50 and a heat-resistant layer 51 formed on one surface of the substrate layer 50, and the positive electrode 11 is arranged on the upper side of the separator 13, and the negative electrode 12 is arranged on the lower side. That is, in the electrode body 14, the heat-resistant layer 51 faces the positive electrode 11, and the substrate layer 50 faces the negative electrode 12. It should be noted that the separator 13 is not limited to Figure 2 In the example shown, the base layer 50 may have the heat-resistant layer 51 on both surfaces. In this case, the heat-resistant layer 51 faces both the positive electrode 11 and the negative electrode 12. The heat-resistant layer 51 is formed on substantially the entire area of one surface of the base layer 50, for example.
[0064] The thickness T1 of the substrate layer 50 and the thickness T2 of the heat-resistant layer 51 satisfy the relationship of T2 / T1≥0.2. As a result, the dissolution of metals such as Ni from the positive electrode 11 is suppressed, and the high-temperature storage characteristics are improved. When T2 / T1<0.2, the effect of the heat-resistant layer 51 described later is not reflected, and the high-temperature storage characteristics cannot be fully improved. The upper limit value of T2 / T1 is, for example, 0.5. T1 is, for example, 5μm to 50μm, and the thickness of T2 is, for example, 1μm to 10μm.
[0065] As the base material layer 50, for example, a porous sheet having ion permeability and insulation is used. Specific examples of the porous sheet include microporous films, woven fabrics, nonwoven fabrics, etc. As the material of the base material layer 50, polyolefins such as polyethylene, polypropylene, copolymers of ethylene and α-olefins, acrylic resins, polystyrene, polyester, cellulose, etc. can be exemplified.
[0066] The heat-resistant layer 51 may include a ceramic-containing polymer containing ceramics and a polymer, or may also include a polymer having an amide bond. The ceramic-containing polymer improves heat resistance by containing ceramics. In addition, the polymer having an amide bond has excellent heat resistance. By placing the heat-resistant layer 51 opposite to the positive electrode 11, the oxidation of the separator 13 is suppressed and the high-temperature storage characteristics can be specifically improved. In addition, by providing the heat-resistant layer 51, the shape of the separator 13 is maintained during abnormal heating of the battery, and the occurrence of internal short circuits can be suppressed. It should be noted that, within the scope of not impairing the purpose of the present disclosure, the heat-resistant layer 51 may also include polymers other than the ceramic-containing polymer and the polymer having an amide bond, but the heat-resistant layer 51 is preferably formed only by these polymers.
[0067] Examples of ceramics constituting the ceramic-containing polymer include metal oxide particles, metal nitride particles, metal fluoride particles, and metal carbide particles. Examples of metal oxide particles include aluminum oxide (alumina), titanium oxide (titanium dioxide), magnesium oxide, zirconium oxide, nickel oxide, silicon oxide (silicon dioxide), and manganese oxide. Examples of metal nitride particles include titanium nitride, boron nitride, aluminum nitride, magnesium nitride, and silicon nitride. Examples of metal fluoride particles include aluminum fluoride, lithium fluoride, sodium fluoride, magnesium fluoride, calcium fluoride, and barium fluoride. Examples of metal carbide particles include silicon carbide, boron carbide, titanium carbide, and tungsten carbide. In addition, the inorganic particles 32 may be zeolite (M 2 / n O·Al2O3·xSiO2·yH2O, M is a metal element, n is the valence of M, x≥2, y≥0) and other porous aluminosilicates, talc (Mg3Si4O 10 (OH)2) and other layered silicates, barium titanate (BaTiO3), strontium titanate (SrTiO3) and other minerals, etc. These may be used alone or in combination of two or more.
[0068] The ceramic constituting the ceramic-containing polymer preferably includes at least one selected from the group consisting of alumina, silica, and titania.
[0069] The content of ceramic in the heat-resistant layer 51 is preferably 20 mass % to 95 mass %, more preferably 30 mass % to 70 mass %, relative to the total mass of the heat-resistant layer 51. This improves the permeability of the nonaqueous electrolyte.
[0070] The polymer constituting the ceramic-containing polymer has the function of bonding the respective ceramics to each other and bonding the ceramics to the base layer 50. The polymer can be exemplified by fluorine-based resins such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyimide-based resins, polyamide-based resins, acrylic resins, polyolefin-based resins, styrene-butadiene rubber (SBR), nitrile rubber (NBR), carboxymethyl cellulose (CMC) or its salt, polyacrylic acid (PAA) or its salt, polyvinyl alcohol (PVA), etc. These can be used alone or in combination of two or more.
[0071] The polymer having an amide bond contained in the heat-resistant layer 51 is, for example, a mixture of a para-aramid resin and a meta-aramid resin, or a copolymer containing a para-aramid skeleton and a meta-aramid skeleton. When the polymer having an amide bond is a mixture of a para-aramid resin and a meta-aramid resin, the mass ratio of the para-aramid resin to the meta-aramid resin constituting the polymer having an amide bond is preferably 40:60 to 90:10, and more preferably 50:50 to 75:25. When the polymer having an amide bond is a copolymer containing a para-aramid skeleton and a meta-aramid skeleton, the mass ratio of the para-aramid skeleton to the meta-aramid skeleton constituting the polymer having an amide bond is preferably 40:60 to 90:10, and more preferably 50:50 to 75:25. When the heat-resistant layer 51 contains a polymer having an amide bond, the heat-resistant layer 51 may further contain the above-mentioned ceramics.
[0072] The heat-resistant layer 51 can be formed by applying a solution containing a ceramic polymer or a solution of a polymer having an amide bond to the surface of the substrate layer 50. As a coating method (film forming method) of the polymer solution, for example, die extrusion, rod coating, dipping, etc. can be listed. After the resin solution is applied to the surface of the substrate layer 50, the coating film can be dried to remove the solvent, or the substrate layer 50 can be immersed in a coagulation tank to remove the solvent. The coagulation tank can use a solvent used in the resin solution and water that is inactive and compatible with the solvent.
[0073] Example
[0074] Hereinafter, the present disclosure will be further described based on examples, but the present disclosure is not limited to these examples.
[0075] <Example 1>
[0076] [Preparation of positive electrode active material]
[0077] The [Ni 0.90 Al 0.05 Mn 0.05 The composite hydroxide represented by ](OH)2 was calcined at 500°C for 8 hours to obtain an oxide (Ni 0.90 Al 0.05 Mn 0.05 Next, LiOH and the composite oxide were mixed so that the molar ratio of Li to the total amount of Ni, Al and Mn was 1.03:1 to obtain a mixture. The mixture was placed under an oxygen gas flow with an oxygen concentration of 95% (per 10 cm 3 The mixture was calcined at a rate of 2 mL / min and a flow rate of 5 L / min per kg of the mixture) from room temperature to 650°C at a heating rate of 2.0°C / min, and then calcined from 650°C to 780°C at a heating rate of 0.5°C / min to obtain a lithium-containing composite oxide.
[0078] Water is added to the obtained lithium-containing composite oxide to make the slurry concentration become 1500g / L, stirred for 15 minutes, and filtered to obtain a cake-like composition. Powdered lithium methanesulfonate is added to the cake-like composition. The amount of lithium methanesulfonate added is 0.1% by mass relative to the total mass of the lithium-containing composite oxide. After adding lithium methanesulfonate, it is dried under a vacuum atmosphere at 180°C for 2 hours to obtain a positive electrode active material. It should be noted that the presence of lithium methanesulfonate on the particle surface of the composite oxide was confirmed by Fourier transform infrared spectroscopy (FT-IR).
[0079] [Production of positive electrode]
[0080] The positive electrode active material, acetylene black and polyvinylidene fluoride are mixed in a mass ratio of 98:1:1, and N-methyl-2-pyrrolidone (NMP) is used as a dispersion medium to prepare a positive electrode mixture slurry. Next, the positive electrode mixture slurry is applied to the positive electrode core formed by aluminum foil, and after the coating is dried and compressed, the positive electrode core is cut into a specified electrode size to obtain a positive electrode having a positive electrode mixture layer formed on both sides of the positive electrode core. It should be noted that an exposed portion exposed on the surface of the positive electrode core is provided on a part of the positive electrode.
[0081] [Production of negative electrode]
[0082] A mixture of 99 parts by mass of artificial graphite and 1 part by mass of silicon oxide (SiO) is used as the negative electrode active material. 100 parts by mass of the mixture, 1 part by mass of carboxymethyl cellulose (CMC) and 1 part by mass of styrene butadiene rubber (SBR) are mixed, and an appropriate amount of water is added to prepare a negative electrode mixture slurry. Next, the negative electrode mixture slurry is applied to the negative electrode core formed by copper foil, and after the coating is dried and compressed, the negative electrode core is cut into a specified electrode size, and a negative electrode having a negative electrode mixture layer formed on both sides of the negative electrode core is produced. It should be noted that an exposed portion exposed on the surface of the negative electrode core is provided on a part of the negative electrode.
[0083] [Production of separators]
[0084] Using para-phenylenediamine and terephthaloyl dichloride as raw materials, a polycondensation reaction is carried out in NMP to prepare a solution of a para-aramid resin with a solid content concentration of 3% by mass. In addition, as a meta-aramid resin, a powder of polyisophthalamide (Conex, manufactured by Teijin Co., Ltd.) is used, and 10 parts by mass of the powder is dissolved in 90 parts by mass of NMP to prepare a solution of a meta-aramid resin. The para-aramid resin and the meta-aramid resin are mixed in a mass ratio of 40:60 to prepare a coating liquid for a heat-resistant layer. The coating liquid is applied to one side of a porous substrate (thickness 10 μm) made of polyethylene, and immersed in ion exchange water to solidify it. Then, it is washed with running water of ion exchange water, dried to remove moisture, and thus a separator is obtained. The ratio (T2 / T1) of the thickness T2 of the heat-resistant layer to the thickness T1 of the substrate layer is 0.4.
[0085] [Preparation of non-aqueous electrolyte]
[0086] LiPF6 was dissolved at a concentration of 1.2 mol / L in a mixed solvent of ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) in a volume ratio of 3:3:4 (25°C) to prepare a non-aqueous electrolyte.
[0087] [Production of test battery cell (secondary battery)]
[0088] Separately, an aluminum lead is installed on the exposed portion of the positive electrode, and a nickel lead is installed on the exposed portion of the negative electrode, so that the positive electrode and the negative electrode are wound into a spiral shape through a separator to produce a wound electrode body. At this time, the heat-resistant layer of the separator is opposite to the positive electrode. Insulating plates are arranged above and below the electrode body, and the electrode body is housed in an outer can. Separately, the negative electrode lead is welded to the bottom of the outer can with a bottomed cylindrical shape, and the positive electrode lead is welded to the sealing body. The electrolyte is injected into the outer can, and the opening of the outer can is sealed through the sealing body through a gasket to produce a secondary battery as a test battery cell.
[0089] [Evaluation of capacity retention rate after high-temperature storage]
[0090] The test battery cell was charged at a constant current of 0.3C until the battery voltage reached 4.2V under an environment of 25°C, and then charged at a constant voltage of 4.2V until the current value reached 0.02C. Then, the battery was discharged at a constant current of 0.5C until the battery voltage reached 2.5V, and the discharge capacity at this time was taken as the initial discharge capacity.
[0091] For the test battery cell, in an environment of 25°C, the battery voltage was charged at a constant current of 0.3C until it reached 4.2V, and then the battery voltage was charged at a constant voltage of 4.2V until the current value reached 0.02C. Furthermore, after standing for 2 months in an environment of 60°C, the battery voltage was left standing for 12 hours in an environment of 25°C, and then the battery voltage was discharged at a constant current of 0.5C until it reached 2.5V. Then, for the test battery cell, in an environment of 25°C, the battery voltage was charged at a constant current of 0.3C until it reached 4.2V, and then the battery voltage was charged at a constant voltage of 4.2V until the current value reached 0.02C. Furthermore, the battery voltage was discharged at a constant current of 0.5C until it reached 2.5V, and the discharge capacity at this time was taken as the discharge capacity after storage. From the above-mentioned initial discharge capacity and discharge capacity after storage, the capacity retention rate after high-temperature storage was calculated according to the following formula.
[0092] Capacity retention rate after high temperature storage (%) = (discharge capacity after storage - initial discharge capacity) / initial discharge capacity × 100
[0093] <Example 2>
[0094] In the preparation of the positive electrode active material, a test cell was prepared and evaluated in the same manner as in Example 1 except that the amount of lithium methanesulfonate added was 0.3 mass % relative to the total mass of the lithium-containing composite oxide.
[0095] <Example 3>
[0096] In the preparation of the positive electrode active material, the addition amount of lithium methanesulfonate relative to the total mass of the lithium-containing composite oxide was set to 0.5 mass %, and in the preparation of the separator, the coating amount of the coating liquid was adjusted to produce a separator with T2 / T1 of 0.22. Otherwise, a test battery cell was prepared and evaluated in the same manner as Example 1.
[0097] <Example 4>
[0098] In the preparation of the positive electrode active material, a test cell was prepared and evaluated in the same manner as in Example 1 except that the amount of lithium methanesulfonate added was 0.5 mass % based on the total mass of the lithium-containing composite oxide.
[0099] <Example 5>
[0100] In the preparation of the positive electrode active material, the addition amount of lithium methanesulfonate relative to the total mass of the lithium-containing composite oxide was set to 0.5 mass %, and in the preparation of the separator, the coating amount of the coating liquid was adjusted to prepare a separator with T2 / T1 of 0.5. Otherwise, a test battery cell was prepared and evaluated in the same manner as Example 1.
[0101] <Example 6>
[0102] A test cell was prepared and evaluated in the same manner as in Example 1 except that the amount of lithium methanesulfonate added was 0.5 mass % relative to the total mass of the lithium-containing composite oxide in the preparation of the positive electrode active material and the following changes were made in the preparation of the separator.
[0103] (1) A coating liquid was prepared by dispersing 5 parts by mass of polyvinyl alcohol (PVA) and 5 parts by mass of alumina in 90 parts by mass of NMP.
[0104] (2) The coating liquid was applied to one surface of a polyethylene porous substrate (thickness 10 μm), and the coating was dried to form a heat-resistant layer. The ratio (T2 / T1) of the thickness T2 of the heat-resistant layer to the thickness T1 of the substrate layer was 0.4.
[0105] <Example 7>
[0106] In the preparation of the positive electrode active material, a test cell was prepared and evaluated in the same manner as in Example 1 except that the amount of lithium methanesulfonate added was 1 mass % relative to the total mass of the lithium-containing composite oxide.
[0107] <Example 8>
[0108] In the preparation of the positive electrode active material, sodium methanesulfonate was used instead of lithium methanesulfonate, and the addition amount of sodium methanesulfonate was set to 0.5 mass % based on the total mass of the lithium-containing composite oxide. A test cell was prepared and evaluated in the same manner as in Example 1.
[0109] <Example 9>
[0110] In the preparation of the positive electrode active material, a test cell was prepared and evaluated in the same manner as in Example 1 except that lithium ethanesulfonate was used instead of lithium methanesulfonate and the amount of lithium ethanesulfonate added was 0.5 mass % relative to the total mass of the lithium-containing composite oxide.
[0111] <Comparative Example 1>
[0112] A test cell was prepared and evaluated in the same manner as in Example 1 except that lithium methanesulfonate was not added in the preparation of the positive electrode active material and the coating amount of the coating liquid was adjusted in the preparation of the separator to prepare a separator having T2 / T1 of 0.22.
[0113] <Comparative Example 2>
[0114] A test cell was prepared and evaluated in the same manner as in Example 1 except that lithium methanesulfonate was not added in the preparation of the positive electrode active material and the coating amount of the coating liquid was adjusted in the preparation of the separator to prepare a separator having T2 / T1 of 0.4.
[0115] <Comparative Example 3>
[0116] A test cell was prepared and evaluated in the same manner as in Example 1 except that lithium methanesulfonate was not added in the preparation of the positive electrode active material and the coating amount of the coating liquid was adjusted in the preparation of the separator to prepare a separator having T2 / T1 of 0.5.
[0117] <Comparative Example 4>
[0118] A test cell was produced and evaluated in the same manner as in Example 1 except that lithium methanesulfonate was not added in the production of the positive electrode active material and that a heat-resistant layer was not formed in the production of the separator.
[0119] <Comparative Example 5>
[0120] In the preparation of the positive electrode active material, a test cell was prepared and evaluated in the same manner as in Example 1 except that lithium succinate was added instead of methanesulfonic acid and the amount of lithium succinate added was 0.5 mass % relative to the total mass of the lithium-containing composite oxide.
[0121] <Comparative Example 6>
[0122] In the preparation of the positive electrode active material, a test cell was prepared and evaluated in the same manner as in Example 1 except that lithium oxalate was added instead of methanesulfonic acid and the amount of lithium oxalate added was 0.5 mass % relative to the total mass of the lithium-containing composite oxide.
[0123] <Comparative Example 7>
[0124] A test cell was prepared and evaluated in the same manner as in Example 1 except that the amount of lithium methanesulfonate added was 0.5 mass % relative to the total mass of the lithium-containing composite oxide in the preparation of the positive electrode active material and that the heat-resistant layer was not formed in the preparation of the separator.
[0125] <Comparative Example 8>
[0126] In the preparation of the positive electrode active material, the addition amount of lithium methanesulfonate relative to the total mass of the lithium-containing composite oxide was set to 0.5 mass %, and in the preparation of the separator, 10 mass parts of polyvinylidene fluoride (PVDF) powder was dissolved in 90 mass parts of NMP, and the obtained PVDF solution was used as a coating liquid for the heat-resistant layer. Otherwise, a test battery cell was prepared and evaluated in the same manner as in Example 1.
[0127] <Comparative Example 9>
[0128] A test cell was prepared and evaluated in the same manner as in Example 1 except that lithium methanesulfonate was not added in the preparation of the positive electrode active material and the coating amount of the coating liquid was adjusted in the preparation of the separator to prepare a separator having T2 / T1 of 0.14.
[0129] Evaluation results of the test cells of Examples and Comparative Examples are shown in Table 1. The capacity retention rate after high-temperature storage of each test cell shown in Table 1 is a relative value when the value of the test cell of Comparative Example 1 is 100, and a larger value indicates better high-temperature storage characteristics.
[0130] [Table 1]
[0131]
[0132] As shown in Table 1, the test battery cells of the embodiments have superior high-temperature storage characteristics compared to the test battery cells of the comparative examples. From the results of the test battery cells of Examples 1, 2, 4, and 7, it can be seen that when the addition amount of the methanesulfonic acid compound is about 0.5 mass %, the improvement in high-temperature storage characteristics is the highest. In addition, from the results of the test battery cells of Examples 3 to 5, it can be seen that when T2 / T1 is about 0.4, the improvement in high-temperature storage characteristics is the highest. In addition, from the results of the test battery cells of Examples 4, 8, and 9, it can be seen that as the sulfonic acid compound, lithium methanesulfonate is preferred. In addition, from the results of the test battery cells of Examples 4 and 6, it can be seen that the ceramic-containing polymer and the polymer having an amide bond as the heat-resistant layer have approximately the same high-temperature storage characteristics.
[0133] On the other hand, the test cells of Comparative Examples 1 to 3, in which the positive electrode did not use the sulfonic acid compound, had poorer high-temperature storage characteristics than the test cells of Examples 3 to 5. In addition, the test cell of Comparative Example 7, in which a separator without a heat-resistant layer was used, and the test cell of Comparative Example 8, in which a separator made of a coating liquid not containing a predetermined polymer was used, also had poorer high-temperature storage characteristics than the test cells of Examples 3 to 5. In particular, the test cell of Comparative Example 4, in which the positive electrode did not use the sulfonic acid compound and the separator without a heat-resistant layer was used, had further poorer high-temperature storage characteristics than Comparative Examples 1 to 3. In addition, the test cells of Comparative Examples 5 and 6, in which lithium succinate or lithium oxalate was used instead of the sulfonic acid compound, had equivalent high-temperature storage characteristics to the test cell of Comparative Example 2, in which no acid salt was added to the positive electrode. In addition, the test cell of Comparative Example 9, in which a separator having a heat-resistant layer T2 / T1 of less than 0.2 was used, had substantially equivalent high-temperature storage characteristics to the test cell of Comparative Example 7, in which a separator without a heat-resistant layer was used.
[0134] Based on the above results, it is understood that when a specific sulfonic acid compound is used in a positive electrode and a predetermined separator is used, a specific synergistic effect is exhibited, and a non-aqueous electrolyte secondary battery with improved high-temperature storage characteristics can be realized.
[0135] The present disclosure is further described through the following embodiments.
[0136] Composition 1:
[0137] A non-aqueous electrolyte secondary battery comprises a positive electrode, a negative electrode, a separator for separating the positive electrode and the negative electrode from each other, and a non-aqueous electrolyte.
[0138] The positive electrode comprises a lithium-containing composite oxide and a sulfonic acid compound present on the surface of particles of the lithium-containing composite oxide.
[0139] The aforementioned sulfonic acid compound is a compound represented by formula (I),
[0140] The separator comprises a substrate layer and a heat-resistant layer formed on a surface of the substrate layer, wherein the heat-resistant layer faces the positive electrode.
[0141] The thickness T1 of the base material layer and the thickness T2 of the heat-resistant layer satisfy the relationship of T2 / T1≥0.2.
[0142]
[0143] (In the formula, A is a Group 1 or Group 2 element, R is a hydrocarbon group, and n is 1 or 2.)
[0144] Composition 2:
[0145] The nonaqueous electrolyte secondary battery according to Configuration 1, wherein A is a Group 1 element.
[0146] Composition 3:
[0147] The nonaqueous electrolyte secondary battery according to Configuration 1, wherein A is Li.
[0148] Composition 4:
[0149] The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 3, wherein R is an alkyl group.
[0150] Composition 5:
[0151] The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 3, wherein R is a methyl group.
[0152] Composition 6:
[0153] The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 5, wherein the amount of the sulfonic acid compound present on the surface of the lithium-containing composite oxide is 2% by mass or less based on the mass of the lithium-containing composite oxide.
[0154] Composition 7:
[0155] The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 6, wherein the lithium-containing composite oxide has a layered rock salt structure.
[0156] Composition 8:
[0157] The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 7, wherein the heat-resistant layer includes a ceramic-containing polymer containing a ceramic and a polymer.
[0158] Composition 9:
[0159] In the nonaqueous electrolyte secondary battery according to Configuration 8, the content of the ceramic in the heat-resistant layer is 20 mass % or more and 95 mass % or less relative to the total mass of the heat-resistant layer.
[0160] Composition 10:
[0161] The nonaqueous electrolyte secondary battery according to configuration 8 or 9, wherein the ceramic includes at least one selected from the group consisting of alumina, silica, and titania.
[0162] Composition 11:
[0163] The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 7, wherein the heat-resistant layer includes a polymer having an amide bond.
[0164] Composition 12:
[0165] In the nonaqueous electrolyte secondary battery according to Configuration 11, the heat-resistant layer further includes ceramics.
[0166] Composition 13:
[0167] The nonaqueous electrolyte secondary battery according to any one of configurations 1 to 12, wherein the lithium-containing composite oxide is composed of the general formula Li a Ni x Co y M z O 2-b (wherein, 0.95≤a≤1.2, 0.80≤x≤0.95, 0≤y≤0.20, 0≤z≤0.20, 0≤b≤0.05, x+y+z=1, and M is at least one element selected from the group consisting of Al, Mn, Fe, Ti, Si, Nb, Mo, W and Zn.)
[0168] Composition 14:
[0169] The nonaqueous electrolyte secondary battery according to Configuration 13, wherein x in the general formula satisfies 0.87≤x≤0.95.
[0170] Description of Reference Numerals
[0171] 10 non-aqueous electrolyte secondary battery, 11 positive electrode, 12 negative electrode, 13 separator, 14 electrode body, 16 outer can, 17 sealing body, 18, 19 insulating plate, 20 positive electrode lead, 21 negative electrode lead, 22 groove portion, 23 internal terminal plate, 24 lower valve body, 25 insulating member, 26 upper valve body, 27 cover, 28 gasket, 30 positive electrode core body, 31 positive electrode mixture layer, 40 negative electrode core body, 41 negative electrode mixture layer, 50 base material layer, 51 heat-resistant layer.
Claims
1. A non-aqueous electrolyte secondary battery comprising a positive electrode, a negative electrode, a separator for separating the positive electrode and the negative electrode from each other, and a non-aqueous electrolyte, The positive electrode comprises a lithium-containing composite oxide and a sulfonic acid compound present on the surface of particles of the lithium-containing composite oxide. The sulfonic acid compound is a compound represented by formula (I), The separator includes a base layer and a heat-resistant layer formed on a surface of the base layer, wherein the heat-resistant layer faces the positive electrode. The thickness T1 of the substrate layer and the thickness T2 of the heat-resistant layer satisfy the relationship T2 / T1≥0.2, In the formula, A is a Group 1 or Group 2 element, R is a hydrocarbon group, and n is 1 or 2.
2. The nonaqueous electrolyte secondary battery according to claim 1, wherein The A is a Group 1 element.
3. The nonaqueous electrolyte secondary battery according to claim 1, wherein The A is Li.
4. The nonaqueous electrolyte secondary battery according to claim 1, wherein The R is an alkyl group.
5. The nonaqueous electrolyte secondary battery according to claim 1, wherein The R is a methyl group.
6. The nonaqueous electrolyte secondary battery according to claim 1, wherein The amount of the sulfonic acid compound present on the surface of the lithium-containing composite oxide is 2 mass % or less relative to the mass of the lithium-containing composite oxide.
7. The nonaqueous electrolyte secondary battery according to claim 1, wherein The lithium-containing composite oxide has a layered rock salt structure.
8. The nonaqueous electrolyte secondary battery according to claim 1, wherein The heat-resistant layer includes a ceramic-containing polymer containing ceramic and a polymer.
9. The nonaqueous electrolyte secondary battery according to claim 8, wherein The content of the ceramic in the heat-resistant layer is 20 mass % or more and 95 mass % or less relative to the total mass of the heat-resistant layer.
10. The nonaqueous electrolyte secondary battery according to claim 8, wherein The ceramic includes at least one selected from the group consisting of alumina, silica, and titania.
11. The nonaqueous electrolyte secondary battery according to claim 1, wherein The heat-resistant layer includes a polymer having an amide bond.
12. The nonaqueous electrolyte secondary battery according to claim 11, wherein The heat-resistant layer further comprises ceramics.
13. The nonaqueous electrolyte secondary battery according to claim 1, wherein The lithium-containing composite oxide has a general formula of Li a Ni x Co y M z O 2-b Represents, wherein 0.95≤a≤1.2, 0.80≤x≤0.95, 0≤y≤0.20, 0≤z≤0.20, 0≤b≤0.05, x+y+z=1, and M is at least one element selected from the group consisting of Al, Mn, Fe, Ti, Si, Nb, Mo, W and Zn.
14. The nonaqueous electrolyte secondary battery according to claim 13, wherein In the general formula, x is 0.87≤x≤0.95.
Citation Information
Patent Citations
Lithium titanate powder for power storage device electrode, active substance material, and power storage device using the active substance material
JP2018006164A